Eco-friendly electrolytes via a robust bond design for high-energy Li metal batteries. Issue 10 (16th September 2022) - Huang, Yiqiang; Li, Ruhong; Weng, Suting; Zhang, Haikuo; Zhu, Chunnan; Lu, Di; Sun, Chuangchao; Huang, Xiaoteng; Deng, Tao; Fan, Liwu; Chen, Lixin; Wang, Xuefeng; et al.
Abstract : This work proposes a Si–O bond strategy to enhance the electrochemical stability of solvents, pioneering the direction of less-fluorinated electrolytes for eco-friendly and practical Li metal batteries. Abstract : Electrolyte innovation that enables the formation of an anion-derived inorganic-rich solid electrolyte interphase (SEI) on electrodes and possesses wide electrochemical stability is critical for the commercialization of Li metal batteries (LMBs). While recent breakthroughs have improved the battery performance, no eco-friendly and economical less-fluorinated electrolytes can yet meet the practical requirements. Herein, we report a family of siloxane solvents, in which Si–O bonds confer high compatibility to Li metal anodes and high oxidation stability to cathodes simultaneously. The 1.5 M LiFSI in a dimethyldimethoxysilane electrolyte without any additives/cosolvents enables Li metal to achieve a high plating/stripping Coulombic efficiency (CE) of ∼99.8% as well as high-voltage LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) and LiCoO2 (LCO) to achieve a high CE of >99.9%, allowing 4.5 V LiCoO2 (3 mA h cm −2 )||Li (20 μm) cells to retain 95% capacity after 200 cycles and 1.4 A h NCM811 (3.6 mA h cm −2 )||Li (20 μm) pouch cells with 2.5 g A h −1 lean electrolyte to achieve 96% capacity retention after 140 cycles. This work represents a deviation from the highly fluorinated electrolyte pathway for LMBs that not only benefits practical and sustainable LMBs but also highlights the possibility of bond design for developing high-performance electrolyte solutions.